2022
DOI: 10.1167/iovs.63.10.4
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Extraocular Muscle Innervation Is Present Before Eye Opening in a Mouse Model of Infantile Nystagmus Syndrome

Abstract: Purpose To determine if extraocular muscles (EOMs) from mice with nystagmus show abnormalities in myofiber composition and innervation, as seen in EOMs from human nystagmus patients, and to determine when in development those changes occur. Methods Balb/c albino mice were crossed to pigmented mice to generate heterozygous mice, which were mated to create experimental litters containing albinos and wild-type controls. Orbits were harvested from adult animals (12 weeks ol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 59 publications
(63 reference statements)
0
1
0
Order By: Relevance
“…We previously showed that EOMs in albino animals with nystagmus have decreased innervation and an increased proportion of slow myofibers. 11 Changes in NMJ density are seen as early as P10, and increased slow myofiber percentage as early as P14. In that study, we examined only LR and MR, not vertical muscles.…”
Section: Discussionmentioning
confidence: 97%
“…We previously showed that EOMs in albino animals with nystagmus have decreased innervation and an increased proportion of slow myofibers. 11 Changes in NMJ density are seen as early as P10, and increased slow myofiber percentage as early as P14. In that study, we examined only LR and MR, not vertical muscles.…”
Section: Discussionmentioning
confidence: 97%